LIQUID CRYSTAL FILM - CHANG JUN WON; LEE DAE HEE; PARK MOON SOO (2012)
A liquid crystal film (LCF) is provided. The exemplified LCF can be used as a reflective polarization plate, which can improve luminance and light utilization efficiency of a display device, such as an LCD, and the like.